A new species of Sybistroma Meigen (Diptera: Dolichopodidae) from the Middle East with a key to West-Palaearctic species of the genus - Grichanov, Igor Ya.; Kazerani, Farzaneh (Zootaxa, 2014)
A new species, Sybistroma occidasiatica sp. nov., from the Middle East is described. It is close to S. inornata (Loew, 1857), but is distinguished by its long arista-like antennal stylus (longer than postpedicel) and short apicoventral epandrial lobe of the hypopygium (much shorter than cercus). The new species is peculiar in comprising two phenotypes, which can be distinguished by the length ratio of 1st and 2nd articles of the antennal stylus. The following recombination is also proposed: Sybistroma caudata (Loew, 1859), comb. nov. (transferred from Gymnopternus Loew, 1857). A checklist of the 26 West-Palaearctic species of the genus is compiled, as well as a key based mainly on male secondary sexual characters. The known distribution of Sybistroma Meigen, 1824, is discussed.